Synthesizing Jakarta City’s Local Wisdom: Reimagining Sidewalks with an Emotional Design and Sustainability Approach - Limano, Ferric (Bina Nusantara University, 2024)
The research objective was to design sidewalks as walking facilities and public spaces, considering comfort, safety, cleanliness, and functionality for Jakarta’s residents. The city of Jakarta, as a megapolitan center, hosted various societal activities. The high mobility of Jakarta’s population led to busy sidewalk activities, especially walking, regulated by the Director General of Highways’ guidelines. Walking could help reduce pollution, with Jakarta having the worst pollution in 2023. The research problem, based on 360-degree Google Maps images of sidewalks, was that sidewalks serve not only as footpaths but also as public gathering spaces. The qualitative research method examined digital data on sidewalk use in Jakarta (west, central, south, east, and north). The design process incorporated emotional design (visceral, behavioral, reflective) and three dimensions of sustainability (The Overlapping Spheres Model of Triple Bottom Line/TBL). The result is a 3D sidewalk model using emotional and sustainability design approaches. Synthesis of emotional design interprets visceral (sensory), behavioral (habits), and reflective (values) levels. Synthesis of sustainability includes environmental, social, and economic dimensions, focusing on air quality, water management, and energy efficiency. Social and economic aspects aim to meet Jakarta residents’ basic needs. Ultimately, these recommendations aim to make cities and neighborhoods inclusive, safe, resilient, and sustainable. However, the research is limited to design recommendations without direct implementation. Further research or implementation is needed to address these challenges and ensure Jakarta residents’ future well-being.